The myth of the nation’s savior on Jair Bolsonaro’s Instagram after his 2022 election defeat - Braga, Thales Ernesto Cristino; da Fonseca, André Azevedo [UNESP] (Universidade Estadual de Londrina, 2023)
In 2018, Jair Bolsonaro manipulated political mythologies to establish his public image and won the elections. In 2022, he repeated the strategy, but was defeated and did not recognize the result. After three days of silence, he released a video full of ambiguities. The aim of this research is to analyze, from the perspective of political myths, the comments made by users on Bolsonaro’s first manifestation on Instagram after his defeat in the elections. The method used was documentary analysis. It was concluded that the myths of conspiracy and the heroic savior were the most frequently used narratives, since they evoked the figure of a providential leader capable of saving the country from its enemies.
O mito do Salvador da Pátria no Instagram de Jair Bolsonaro após a derrota eleitoral de 2022
Keywords: campanha eleitoral; election campaign; Jair Bolsonaro; mitologia política; political mythology